Explaining the Concept of Re-experiencing Abusive Relationships - Zinatsadat Mirpour; Mohammadali Rahmani; Shohreh Ghorbanshiroodi (Journal of Holistic Nursing and Midwifery)
Introduction: Choosing an emotional partner is an important occasion that profoundly affects various aspects of life; however, many relationships fail, and people face a vicious cycle of unhealthy and harmful relationships. Objective: This study aimed to explain the concept of re-experiencing harmful relationships. Materials and Methods: This research is a qualitative study done with the Grounded Theory (GT) approach done using the purposive sampling method until data saturation. Data collection methods included semi-structured interviews, observations, and field notes. In this study, 8 victims of harmful relationships and 8 psychologists were interviewed. Each interview lasted 25 to 55 minutes and was digitally recorded. Data analysis was performed along with data collection by Strauss and Corbin’s constant comparative analysis. Using Lincoln and Guba criteria, the accuracy and strength of this research were confirmed. Results: The open coding results indicated that 47 concepts could effectively frame the pattern of re-experiencing unhealthy relationships. In the axial coding stage, the concepts were classified into 8 general categories. Finally, in the selective coding stage, the phenomenon of “harmful relationships” was extracted as a significant category. The central coding paradigm consisted of 8 key features: perceived violence, psychological symptoms, unhealthy relationship strategies, dark personality traits, emotion regulation problems, retention factors, family harms, self-breaking behaviors. Each includes subclasses with specific characteristics. Conclusion: The results showed that harmful relationships are complex, dynamic, continuous, and intervened with the contextual conditions, retention factors, causal conditions, and intervening conditions. So it is necessary to develop and present psychological programs and interventions based on these problems.